Frequency and Clinical Profile of Hypophosphatemic Rickets Among Rachitic Children (Medical Forum Monthly, 2024)
Objective: To determine frequency and clinical profile of hypophosphatemic rickets among rachitic children at N.I.C.H Karachi, Pakistan.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the National Institute of Child Health Karachi, Pakistan from 21st January 2015 to 20th January 2016.Materials and Methods: All consecutive children with age 1 to 14 years of either gender having rickets were enrolled. Hypophosphatemia and its clinical profile like short stature, fractures, family history, bony deformity, joint pain, and dental abnormalities were observed.Results: Out of total 230 rachitic children, frequency of hypophosphatemic rickets were found in 16(7%) rachitic children. The mean age of the patients was 7.56±4.35 years. Majority Gender distribution showed05(31%) were males and 11(69%) were females. Short stature 11(69%), fracture 02(12.5%), joint pain 04(25%), family history of hypophosphatemic rickets was present in 05(31%). Bony deformity and dental abnormalities were found in 07(44%) and 06(37.5%) patients respectively.Conclusion: In this study, short stature is the most common clinical profile, followed by bony deformities and dental abnormalities. A diagnosis of hypophosphatemic rickets should be considered in all patients presenting with short stature, bony deformities along with low serum phosphate and normal iPTH and 25 – hydroxy vitamin D.